Managing conflict in hospitality - Stavridis, Katrina; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2011)
"Dissatisfied customers, miscommunication between staff, alcohol affected patrons, personality clashes: conflict is a daily part of working in hospitality. This is why it is so important that we all have finely tuned conflict management skills. This program will equip hospitality workers with the skills and knowledge they need to handle all forms of conflict with openness, honesty and empathy. We find out how to identify potential causes of conflict and act before the situation escalates. We also discover situational techniques to resolve conflict and learn the importance of follow-up such as incident reports and action plans"--Container.
Writer/director/producer: Katrina Stavridis.
Keywords: Conflict management; Hospitality industry; Hospitality industry -- Employees -- Training of